KUALITAS PAPAN OSB ( Oriented Strand Board ) DARI KAYU KARET (Hevea brasiliensis) BERDASARKAN PANJANG STRAND DAN KADAR PEREKAT - Arifin, Dede; Dirhamsyah, M; Setyawati, Dina (Universitas Tanjungpura, 2018)
The objectives of the research were to analyze the effect of strand length difference, adhesive level and its interaction on physical and mechanical properties of wood rubber OSB board. As well as to analyze the length of the strand and the adhesive level that produces the physical and mechanical properties of the best rubber wood OSB board. The research was conducted at Wood Workshop Laboratory, Wood Processing Laboratory, Faculty of Forestry, University of Tanjungpura and Laboratory of PT. Duta Pertiwi Nusantara Pontianak. The materials used are rubber wood, phenol formaldehyde adhesive (PF) and liquid paraffin. The treatments in this study were strand length was 5 cm, 10 cm and 15 cm, and adhesive content was of 5%, 7%, 9%. OSB boards were made measuring 30 cm x 30 cm x 1cm with a target density of 0.7 gr / cm3. Forged hot with temperature of 160 ÂºC for 7 minutes. The results showed that all of the strand length and adhesive treatments resulted in OSB complying with JIS A 5908-2003 (Base Particleboard Type 24-10) standard, except for water content test in A3B2 treatment and MOE test on treatment A1B1, A1B2. Based on best OSB scoring calculation is rubber wood with strand length 15 cm with 9% adhesive level.Keywords: Adhesive Content, Oriented Strand Board, Quality, Strand Length